Ursolic Acid Ameliorates Diabetic Nephropathy by Inhibiting JAK2/STAT3-Driven Ferroptosis: Mechanistic Insights from Network Pharmacology and Experimental Validation - Zhou Y; Lou C; Xu X; Feng B; Fan X; Wang X (Drug Design, Development and Therapy)
Yijing Zhou,* Chengli Lou,* Xiuqin Xu, Bo Feng, Xiaoping Fan, Xiangjing Wang Department of Nephropathy, Jiaxing Traditional Chinese Medicine Hospital, Jiaxing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yijing Zhou, Email zyj13967332522@163.comPurpose: Ursolic acid (UA) improves diabetic nephropathy (DN), but its regulatory mechanism requires further verification.Methods: The bioactive component-target network of UA in DN was determined using a network pharmacology approach. DN mice (STZ-diabetic C57BL/6 mice, n = 8/group, 4 weeks) were treated with UA (25 mg/kg and 100 mg/kg) and the JAK agonist RO8191 (2 mg/kg). The DN cell model (high glucose-injured NRK-52E cells) was treated with UA (10 and 50 μM) and RO8191 (2 μM) for 24 h. The molecular mechanisms by which UA acts were further verified in vivo and in vitro.Results: UA treatment ameliorated the general state of the DN mouse model, as characterized by the attenuation of weight loss and downregulation of fasting blood glucose (FBG) and fasting serum insulin (FINS) levels (all P < 0.05). Renal pathological changes and impaired renal function (increased levels of Scr, BUN, and UAER) were also improved by UA treatment (all P < 0.05). In vitro, UA increased the viability of DN cells in vitro (P < 0.001). Concurrently, UA remarkably downregulated the levels of ROS, SOD, and iron and up-regulated the levels of MDA, GPX4, and SLC7A11 (all P < 0.05) in vivo and in vitro. Mechanistically, activation of the JAK2-STAT3 pathway with the agonist RO8191 significantly reduced UA’s anti-ferroptosis and anti-oxidative effects of UA.Conclusion: UA protected against DN by blocking JAK2/STAT3-mediated ferroptosis.Keywords: diabetic nephropathy, ursolic acid, JAK2/STAT3 pathway, ferroptosis, network pharmacology